MANAJEMEN ASET SEBAGAI UPAYA MENGOPTIMALISASI ASET TETAP PADA USAHA PERCETAKAN CV. NUSANTARA KREASI BERDASARKAN ISO 55000: ASSET MANAGEMENT HOW TO OPTIMIZE FIXED ASSETS - Fajarhya, Bagus; Ikraam, Ikraam; Dini, Maya (Program Studi Akuntansi Universitas Panca Bhakti, 2025)
Effective fixed asset management is an important element in supporting operational efficiency and sustainability, especially for small businesses such as printing. This study aims to analyze how asset management can optimize the utilization of fixed assets at CV. Nusantara Kreasi, a printing business in Palembang City. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, direct observation, and documentation of the company's operational processes and asset conditions. The results of the study indicate that fixed asset management at CV. Nusantara Kreasi has been carried out simply and has not been systematically documented. Machine maintenance is carried out periodically by the production team but not based on a structured schedule. However, there is awareness from the owner of the importance of maintaining asset conditions to support business productivity. This study also adapts the principles of ISO 55000 in a small business scale, such as value realization, assurance of capability, and lifecycle approach as a basis for developing more targeted and efficient planning steps.